Respuesta :

Answer:

Step-by-step explanation: Step 1: Simplify both sides of the equation.

3(y+8)=36

(3)(y)+(3)(8)=36(Distribute)

3y+24=36

Step 2: Subtract 24 from both sides.

3y+24−24=36−24

3y=12

Step 3: Divide both sides by 3.

3y/3=12/3

y=4

Answer:

y=4

Step-by-step explanation:

3(y+8) = 36

3y + 24 = 36

3y= 12

y=4

1. Distribute the numbers in the parenthesis with the 3

2. Subtract 24 from both sides of the equation

3. Divide each side of the equation by three to isolate your variable.

hope this helps =)

ACCESS MORE